Physical and chemical data of sediment core SWERUS-C3-L2-13-PC - Wiers, Steffen; Snowball, Ian; O'Regan, Matthew; Pearce, Christof; Almqvist, Bjarne (PANGAEA, 2020)
Physical and chemical properties of core SWERUS-C3-L2-13-PC from the Arlis Plateau, Arctic Ocean. The dataset was used to integrate the core into the regional stratigraphy and evaluate its palaeo- and rock magnetic properties in this context. Physical and chemical properties were measured at Stockholm University (Sweden). Magnetic properties were measured at Uppsala University (Sweden).